Making white spots disappear! Do minimally invasive treatments improve incisor opacities in children with molar‐incisor hypomineralisation?. Issue 4 (16th February 2022) - Warner, Claire; Hasmun, Noren N.; Elcock, Claire; Lawson, Jennifer A.; Vettore, Mario V.; Rodd, Helen D.
Abstract: Background: Children with molar‐incisor hypomineralisation (MIH) frequently seek aesthetic treatment for incisor opacities. Surprisingly, few studies have evaluated the clinical success of such interventions. Aim: To quantify the effectiveness of minimally invasive treatments in reducing enamel opacity visibility in children with MIH. Design: This in vitro study used digital clinical images of 23 children aged 8–16 years with MIH who underwent microabrasion and/or resin infiltration for the management of incisor opacities. Standard images were taken pre‐treatment and 6 months post‐treatment. Image software (Image‐Pro Plus ® V7) was employed to convert 24‐bit RGB images to 16‐bit greyscale and 145× magnification. Measurement repeatability was assessed using intra‐class correlation coefficients (ICCs). Post‐treatment changes in visible opacity area (mm 2 ) and brightness (greyscale value) were tested using the Wilcoxon signed‐rank test for related samples. Results: The mean total opacity surface area significantly reduced from 14.3 mm 2 (SD = 7.5) to 9.4 mm 2 (SD = 9.0) post‐treatment. The proportion of tooth surface affected by the opacity also significantly reduced from 22.5% (SD = 10.5) to 14.7% (SD = 12.7). The mean maximum opacity brightness significantly reduced from 53 066 greyscale value (SD = 4740) to 49 040 (SD = 3796). ICC was good/excellent (0.75–1.0). Conclusion: Minimally invasive treatment is effective in reducing the size and brightness of discrete incisor opacities. Future research should compare objective findings with patient‐reported outcomes.